Grave of the lawgiver - Tremayne, Peter (Tremayne, Peter. Sister Fidelma novels, 2025)
Autumn, AD 673. Fidelma accompanies Eadulf to his hometown, Seaxmund's Ham in the Kingdom of the East Angles, to be greeted with the shocking news that Eadulf's uncle, Athelnoth, the lawgiver, has been murdered and his house burnt down. And Eadulf's younger sister is missing. The locals accuse Fidelma and Eadulf of the crimes, and Fidelma's safety is threatened by the first council of the bishops and kings of the Angles and Saxons, who wish to expel all Hibernian missionaries and teachers from the kingdoms. Against this opposition, Fidelma and Eadulf must unite to solve one of their most complex mysteries yet. Sister Fidelma returns in Grave of the Lawgiver, the thirty-sixth Celtic mystery by Peter Tremayne, acclaimed author of Prophet of Blood, Death of a Heretic, and The House of Death. If you love Ellis Peters, you'll be gripped by Grave of the Lawgiver.